National-wide survey of ophthalmic human resources in China in 2021 - Jin-Da Wang; Chang-Xi Chen; Mei-Rui Liu; Li-Jun Zhang; Yan Sun; Kai Cao (BMC Health Services Research)
Abstract Purpose To evaluate the availability of human resources for ophthalmic services in mainland China. Methods In 2021, we conducted a nationwide survey of ophthalmic outpatient services across 2996 tertiary hospitals and 10,404 secondary hospitals in 31 provinces in mainland China. Results The response rate was 73.6% (9856/13400), with 78.7% (7759/9856) providing ophthalmic services. By 2021, the total number of ophthalmologists, ophthalmic nurses, and optometrists was 48,652, 64,495, and 14,320, respectively. The densities (per 50,000 population) were 1.7, 2.25, and 0.47, respectively. The density of ophthalmologists was < 1 only in the XiZang region. The average doctor-patient ratio was 2584.8. In Shanghai and Zhejiang provinces, this ratio exceeded 4000. Conclusion There are currently 1.7 ophthalmologists, 2.25 nurses, and 0.47 optometrists for every 50,000 people in China. The number of ophthalmologists has reached the global average, but the number of optometrists is far below the global average. And the medical pressure across China is uneven, with some provinces such as Shanghai and Zhejiang facing enormous pressure.